Relationship of Prostate Specific Antigen and Digital Rectal Examination in the Prediction of Prostate Cancer - Timilsina, Bhusan Raj; Devkota, Gaurav; Giri, Shweta; Pradhan, Sulav; KC, Sudeep RaJ (Journal of College of Medical Sciences-Nepal, 2020)
Background: Prostate cancer is one of the most common and leading cause of death among different genitourinary causes. However, screening of prostate cancer is limited to Digital Rectal Examination (DRE) and Prostate Specific Antigen (PSA) in Nepal. The aim of this study is to find out which modality is more helpful for the diagnosis of Prostate Cancer. Methods: A retrospective cross-sectional study was conducted in the department of Urology, College of Medical Sciences, Chitwan, Nepal. All patients included in this study were who presented to the OPD with Lower Urinary Tract Symptoms (LUTS). The patients were above the age of 40 with clinical suspicion prostate cancer based on either DRE or PSA. Results: A total of 150 patients were enrolled from April 2019 to April 2020. Their mean± SD age was of 65.18±9.38 years. The accuracy of the diagnostic test for DRE and PSA were cut off at 4, PSA cut off range of 4 to 10, PSA cut off range of 10 to 30 and PSA cut off at 30 showed that all the screening indices were better for DRE (Sensitivity=100%, Specificity=59.2%, Diagnostic Accuracy=62.2%) than for PSA cut off at 4 (Sensitivity=100%, Specificity=27.6%, Diagnostic Accuracy=32.9%). Among various cut off score or ranges for PSA, cut off score at 30 provided the best screening indices with Sensitivity of 66.7%, Specificity of 97.4% and Diagnostic Accuracy of 95.1%. Conclusions: PSA has higher diagnostic accuracy then DRE. Keywords: DRE; LUTS; Prostate cancer; PSA.